2017
DOI: 10.1016/j.seizure.2017.11.006
|View full text |Cite
|
Sign up to set email alerts
|

Parental knowledge and attitudes towards epilepsy –A study from Jordan

Abstract: This study sheds an important light on the current knowledge status and attitudes of parents of children with epilepsy, and is an invaluable tool for tailoring the delivery of information and support resources for families in our region.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
6
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 20 publications
(13 citation statements)
references
References 25 publications
2
6
0
1
Order By: Relevance
“…In congruence with this, a study in the United States reported that the majority of the parents of children with epilepsy in the sample were having deficient knowledge of the definition and nature of epilepsy and its seizures [34]. Similar findings were also reported by Masri et al [35] in a study carried out in Jordan.…”
Section: Discussionsupporting
confidence: 81%
“…In congruence with this, a study in the United States reported that the majority of the parents of children with epilepsy in the sample were having deficient knowledge of the definition and nature of epilepsy and its seizures [34]. Similar findings were also reported by Masri et al [35] in a study carried out in Jordan.…”
Section: Discussionsupporting
confidence: 81%
“…The socio-demographic factors, including gender, age, educational level and income, have been considered as important determinants of the level of KAB [11]. For example, young people have better knowledge regarding hypertension than older people [12]; women have better overall health behaviors than men [13], and people with higher income tend to have more positive attitudes towards managing diseases [14]. Therefore, it is necessary to investigate which of these factors play important roles in the targeted high-risk population.…”
Section: Introductionmentioning
confidence: 99%
“…Our study did not show an association between QoL in children with epilepsy and the level of parental education. In contrast, Masri et al [ 30 ] found that the higher the education level of parents of children with epilepsy, the better the parents’ knowledge of the condition. These authors also showed that there is an association between positive parental attitudes and behaviours towards epilepsy and a higher parental education level.…”
Section: Discussionmentioning
confidence: 96%